2022
DOI: 10.48550/arxiv.2201.12662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fair ranking: a critical review, challenges, and future directions

Abstract: Ranking, recommendation, and retrieval systems are widely used in online platforms and other societal systems, including e-commerce, media-streaming, admissions, gig platforms, and hiring. In the recent past, a large "fair ranking" research literature has been developed around making these systems fair to the individuals, providers, or content that are being ranked. Most of this literature defines fairness for a single instance of retrieval, or as a simple additive notion for multiple instances of retrievals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 122 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…In addition to the issue of bias in online rating systems, there has also been research on the overall fairness of ranking systems on online work platform marketplaces. Some studies have found that the ranking algorithms used by these platforms may favor certain sellers or providers over others, leading to unequal opportunities and outcomes (Elbassuoni et al, 2020a;Patro et al, 2022).…”
Section: Fairnessmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the issue of bias in online rating systems, there has also been research on the overall fairness of ranking systems on online work platform marketplaces. Some studies have found that the ranking algorithms used by these platforms may favor certain sellers or providers over others, leading to unequal opportunities and outcomes (Elbassuoni et al, 2020a;Patro et al, 2022).…”
Section: Fairnessmentioning
confidence: 99%
“…For example, a study by Patro et al (2022) examined the effects of seller characteristics, such as the seller's reputation and the price of their products or services, on search rankings in an online marketplace. The authors found that these characteristics had a significant impact on search rankings, with sellers with higher reputations and lower prices receiving higher positions in the rankings.…”
Section: Fairnessmentioning
confidence: 99%
See 1 more Smart Citation